Transversal reinforcement technology for laminated composites. (2019) - Bukharov, Sergey; Lebedev, Alexander
Abstract: Study contains analysis of spatial arrangement reinforcement structure forming process of semi-finished composite billets. Modified technology of tufting opportunities for industrial use introduced. It may allow to appear wide application a new class of spatial arrangement reinforcement composites – thick-walled materials with adjustable anisotropy and physic-mechanical properties same to convenience laminated composites. Application of presented thick-walled laminates spatial arrangement reinforcement technology will allow production preforms with increased density. Experimentally usage of modified tufting technology approved in carbon–carbon composite transverse preform reinforcement application. Tufting step 5x5mm, preform thickness 50 mm, 0.793 kg/m 3 preform density reached. Modified technology have shown much less fiber damage compare to convenience KSL-tufting.